Competitive Intelligence and SMEs’ Sustainability in Nigeria - Azage, Joseph; Ogbeide , Darlington Osaremwinda (Journal of Entrepreneurship & Business, 2026)
Purpose: The sustainability of small and medium-sized enterprises (SMEs) is crucial to economic growth, particularly in emerging economies where they serve as major drivers of employment, innovation, and income generation. This study examined the influence of competitive intelligence (CI) on the sustainability of SMEs in Edo State, Nigeria. Specifically, it analyzed the effects of five CI dimensions: market, competitor, technological, strategic, and customer intelligence on SME sustainability. The research contributes a multidimensional assessment of CI within a fragile and resource-constrained African context, providing new insights into how intelligence practices operate in informal and volatile business environments. Method: A quantitative cross-sectional survey was conducted among SME owners and managers in Edo State during 2024. Data were obtained from 517 valid responses through structured questionnaires using a snowball sampling technique. Descriptive and inferential statistical analyses were performed with SPSS version 24.0 to test the hypothesized relationships between CI dimensions and SME sustainability. Result: Market, technological, strategic, and customer intelligence exerted significant positive effects on SME sustainability, while competitor intelligence showed a positive but statistically insignificant effect. The study recommended that policymakers and SME stakeholders promote market-driven intelligence systems, digital literacy, and institutional frameworks that enhance information sharing. Strengthening CI capabilities can help SMEs achieve long-term competitiveness and resilience. This study provides empirical and contextual evidence that enriches the understanding of CI-sustainability linkages within emerging economies, where structural and informational constraints shape business outcomes.